Entrepreneurs’ Acceptance of the Costing Skills Course - Amir Hussin, Muhammad Rosni (International Business Education Journal, 2016)
Costing skills are among the critical skills that SME owner-managers should have for managing a successful enterprise. However, Malaysian SME owner-managers still lack costing skills. The current entrepreneurial training programme provided by the government and its agencies lacks a module on costing skills. Thus, this study is conducted to develop a costing skills course within the entrepreneurial training programme conducted by the government. This study employs a practical action research (AR) approach. Practical AR training includes a cyclical process of planning, acting, observing and reflecting. Each stage of practical AR provides feedback for improvement of the next stage. At the acting stage of this research, feedback was collected and this is the focus of this paper. One interesting finding in this paper is the difference in acceptance between rural and urban entrepreneurs of the costing skills course.